Formulation and Antioxidant Activity Evaluation of Aloe Vera Gel Face Mist Using the DPPH Method - Renny Amelia (Program Studi Farmasi, Universitas Ma Chung, 2026)
Skin damage may be caused by metabolic waste products, combustion processes, and free radicals, which require antioxidants both systemically and locally. One source of antioxidants can be obtained from aloe vera gel extract, which contains compounds such as aloin, aloesin, aloe-emodin, and tannins. This study aimed to determine whether aloe vera gel extract could be formulated into a face mist preparation and to evaluate the antioxidant activity of the resulting face mist formulation. One of the benefits of face mist preparations is their ability to refresh and moisturize facial skin while also providing protection against ultraviolet (UV) radiation-induced damage.The aloe vera gel extract face mist formulations were prepared in varying concentrations of 30%, 35%, and 40%, followed by evaluations including organoleptic testing, pH testing, spreadability testing, homogeneity testing, and viscosity testing. Antioxidant activity was evaluated using the DPPH method with a UV-Vis spectrophotometer, using vitamin C as the reference standard. The results demonstrated that aloe vera gel extract could be successfully formulated into face mist preparations at concentrations of 30%, 35%, and 40%. Based on the evaluation results, including organoleptic properties, homogeneity, specific gravity, viscosity, and spreadability, all formulations met the required standards for face mist preparations. The antioxidant activity test results showed that the 30%, 35%, and 40% aloe vera gel extract face mist formulations were classified as strong antioxidants.